Sasirangan cloth as a learning resource for biology subjects in high school lessons in South Kalimantan - Siti Ramdiah; Ria Mayasari; A. Abidinsyah (University of Muhammadiyah Malang, 2024)
Issues in learning, particularly the utilization of learning resources, have not been maximized to facilitate teachers in guiding students to learn certain concepts related to the surrounding environment. This study aims to analyze the motives and colors of Sasirangan as a source of biology learning in high schools and the knowledge of high school biology teachers in Banjarmasin regarding the existence of Sasirangan. This survey research involved 40 sasirangan craftsmen from 20 sasirangan production houses and 38 high school biology teachers in Banjarmasin, South Kalimantan. The instruments used were interview sheets and questionnaires. Data analysis was descriptive using percentage techniques. The results of expert validation indicated that the interview sheets and questionnaires were suitable, with scores of 89.63 and 92.5. sasirangan has great potential to become a source of biology learning, both in terms of motives and natural colors used by craftsmen. However, high school biology teachers in Banjarmasin have not fully utilized and conveyed it as a biology learning resource. While in other statements, teachers stated that they understood and explained that the existence of Sasirangan is very important to be conveyed in biology learning. Some teachers were able to provide information on biology concepts related to the existence of Sasirangan.